How important are Personal Ties, Trust and Tolerance for Life Satisfaction in Europe? - Frank Crowley; Edel Walsh (University College Cork, Spatial and Regional Economic Research Centre (SRERC), 2018)
Many argue that the rise in populist support in Europe and elsewhere stems from people feeling marginalised, distrustful and generally dissatisfied. Against a backdrop of populism, this paper aims to examine the relationship between social capital and life satisfaction using data on 21,000 individuals from 14 European countries obtained from the Life in Transition Survey (2016). Specifically, we test the empirical significance of a novel social capital-wellbeing conceptual framework that incorporates three key dimensions of personal social capital; (i) structural (personal ties), (ii) cognitive (trust) and (iii) tolerance. This latter aspect is the most novel addition of this research to the theoretical and empirical literature as we argue that tolerance acts as a bridging mechanism between trust and ties in affecting overall wellbeing. Using ordered probit models the paper estimates the effect of social capital on life satisfaction by using an index for aggregate personal social capital, as well as separate indices for structural social capital, cognitive social capital and tolerance. The analysis also examines the interaction effects of social capital with individual and place characteristics of respondents. Among the results we find that strong structural ties with friends and family and being a tolerant, trusting individual improves life satisfaction. Of the social capital indicators, we find that trust in institutions has the largest marginal effect on life satisfaction. Also, interaction effects indicate that social capital could be a key ingredient in overcoming income inequalities, health inequalities and spatial inequalities at the individual level. We conclude that societies that fail to invest in social capital may be more politically unstable or more susceptible to widespread intolerance, distrust and ultimately discontent.
Keywords: 330; life satisfaction; social capital; ties; trust; tolerance; Europe